2022
DOI: 10.1186/s13031-022-00437-1
|View full text |Cite
|
Sign up to set email alerts
|

Shifting to Tele-Mental Health in humanitarian and crisis settings: an evaluation of Médecins Sans Frontières experience during the COVID-19 pandemic

Abstract: Background ‘Tele-Mental Health (MH) services,’ are an increasingly important way to expand care to underserved groups in low-resource settings. In order to continue providing psychiatric, psychotherapeutic and counselling care during COVID-19-related movement restrictions, Médecins Sans Frontières (MSF), a humanitarian medical organization, abruptly transitioned part of its MH activities across humanitarian and resource-constrained settings to remote format. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Studies describing these clinical groups report a higher prevalence of certain diagnoses (eg, schizophrenia or schizoaffective disorder) [ 84 ], while others indicated several barriers, such as lack of digital literacy or confidence to make full use of a telephone, and lack of an appropriate device or broadband required to connect with clinicians [ 105 ]. In resource-limited settings during the COVID-19 pandemic, mental health staff working for Médecins Sans Frontières used audio-only platforms for 80% of TMH care interventions [ 106 ]. Despite this, over half of the patients were unreachable using these interventions, mainly due to poor network coverage, lack of communication devices, or lack of a private space at home [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies describing these clinical groups report a higher prevalence of certain diagnoses (eg, schizophrenia or schizoaffective disorder) [ 84 ], while others indicated several barriers, such as lack of digital literacy or confidence to make full use of a telephone, and lack of an appropriate device or broadband required to connect with clinicians [ 105 ]. In resource-limited settings during the COVID-19 pandemic, mental health staff working for Médecins Sans Frontières used audio-only platforms for 80% of TMH care interventions [ 106 ]. Despite this, over half of the patients were unreachable using these interventions, mainly due to poor network coverage, lack of communication devices, or lack of a private space at home [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…In resource-limited settings during the COVID-19 pandemic, mental health staff working for Médecins Sans Frontières used audio-only platforms for 80% of TMH care interventions [ 106 ]. Despite this, over half of the patients were unreachable using these interventions, mainly due to poor network coverage, lack of communication devices, or lack of a private space at home [ 106 ]. For these patients, specific provision of a device or broadband might be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Tele psychiatry is used to follow patients and reduce any unnecessary travel [ 66 ], which can be used as an alternative method to face-to-face therapy, especially in the COVID-19 crisis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In low-resource settings, attempts to use tele-mental health services to reach underserved groups were found to be feasible but were not necessarily suitable for all types of patients and situations [ 34 ]. A large-scale meta-analytic atlas including 173 studies (n = 502,261 individuals) and investigating mental health problems during the COVID pandemic reported that anxiety, depression, and post-traumatic symptoms were more prevalent in LMICs, although this was not specifically a study of HCWs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%